Quality tools application to improve cost management in food and nutrition unit: A case study (Research, Society and Development, 2022)
Quality tools can help companies grow, becoming more profitable by providing better quality products or services. The aim of this research was to carry out a case study in a food and nutrition unit (FNU) located in Minas Gerais state, implementing the use of three quality tools, namely: Pareto analysis, Ishikawa diagram and 5W1H method in order to obtain a better cost control. In this sense, the methodology chosen was qualitative research, and data collection for this study took place through a report extracted from the business management software used by the company. To calculate the cost of foods products, their own invoices were used. After building the ABC curve, it was possible to determine that the most expensive raw materials were meat, vegetables and leafy vegetables. From these results, two Ishikawa diagrams were prepared to identify the possible causes that led to the spending increase on the mentioned products. Thus, two action plans were prepared using the 5W1H methodology. After the implementation of the actions, the average expenditure on the purchase of meats reduced to R$ 76,207.92, and the average expenditure on the purchase of vegetables and leafy vegetables reduced to R$ 35,605.03, a decrease of 5.79% and 11 .69%  respectively. It can be concluded that such cost reductions were satisfactory for the organization, justifying the importance of the applicability of quality tools for the processes improvement in a FNU.